Think Piece: What Education is of Most Worth in a World Where We Are Consuming the Future of our Children? - Wayne Hugo (Environmental Association of Southern Africa, 2016)
This paper argues that we have to radically rethink the purposes of education in a world that is becoming increasingly unequal as global warming intensifies. It argues that our current generation is taking away worthwhile choices and opportunities from our children by handing them a world that will be more unequal (Picketty, 2013) and hotter (Morris, 2010) than it is now. The author used to hold a position that powerful knowledge was a good overarching response to the issues of inequality in education as it enabled learners from poor backgrounds to escape poverty through knowledge. With global increases in warming and inequality, education needs a far more radical response to these issues. This paper constructs an historical argument that shows why powerful knowledge was such a worthwhile outcome of education by reconstructing Spencer's answer to the question 'what knowledge is of most worth?' (1884). He argued that systematic knowledge was of the most worth and this answer has found strong and well-articulated current support in the work of Michael Young and Joe Muller (2013). This answer makes sense in a world that has a high demand for skills and rewards them with decent occupations and remuneration. However, in a world of increasing inequality and deskilling of jobs, powerful knowledge loses some of its power. Furthermore, with the current inability of humanity to control its acceleration towards heat death, education has to take on a far more radicalising function than that which powerful knowledge can provide. This paper does not suggest what ways we can find out of our current tragic mess, and prefers to prolong the moment of despair; although, it does suggest that processes underway and supported by environmental organisations indicate some ways forward.